The Ghost House Company / Mohd Sulhe Asat... [et al.] - Yusuf, Sulaiman; Sahipah, Mursidi; Aduri, Eddy Adrian; Jois, Aderian; Asat, Mohd Sulhe (2013)
Our company's name is The Ghost House, synonym with our business that is a ghost house, where we get inspiration to do this business from the concept of Japanese company that do similar business. But we want to do different thing from that company to make sure that we have our own identity that will recognize by our customer. Ghost House is the place where every customer that we target as our future customer that including family, couple and teenager to enjoy new exciting entertainment. We offer different kind of entertainment that will ours company provide in services industry. The actual idea of Ghost House comes when we saw the 'Rumah Terbalik' in Tamparuli where the owner build a house upside down that we saw very interesting. It attracts people to come and the owner can generate income at first hand. We had found to do Ghost House concept when we so in the internet a Japanese ghost house that are very interesting and there are no such Ghost House in this country. Therefore, we have come to this decision after we made a research and observation in the market where we have planned that we are going to take this opportunities to open a Ghost House as our business background. In this business, we come out with something different as we are providing different Ghost house concept. This concept was introduced because we believe it will give a new experience and create different excitement to our customers.